Proposition of an Objective and Standardized Sustainability Index: An Alternative to ISE B3 - Melo Neto, João José de; Fontgalland, Isabel Lausanne (International Journal of Global Sustainability, 2022)
In Brazil, the financial advances in market in the recently years are visible, the type B3, is in progression. Studies about the difficulty of measuring corporate sustainability, mainly through qualitative research, fail to assess corporate social performance in companies, mainly because biases and heuristics end up altering the perception of decision makers, making conceptions that should be biased. be rational. Through the MAUT multi-criteria decision support method, we propose an alternative sustainable development index to the ISE with information from the financial statements, considering the proposed index efficient and correlated with the other ESG indexes of B3.